Statistical Performance Indicators and Index : A New Tool to Measure Country Statistical Capacity - Dang, Hai-Anh H.; Pullinger, John; Serajuddin, Umar; Stacy, Brian (World Bank, Washington, DC, 2021)
The World Bank’s Statistical Capacity Index has been widely employed to measure country statistical capacity since its inception two decades ago. This paper builds on the existing advantages of the Statistical Capacity Index, conceptually and empirically, to offer new statistical performance indicators and the Statistical Performance Index, which can better measure a country’s statistical performance. The new index has clearer conceptual motivations, employs a stronger mathematical foundation, and significantly expands the number of indicators and countries covered. The paper further provides empirical evidence that illustrates the strong correlation of the new index with other commonly used development indicators of human capital, governance, poverty, and inequality. The framework can accommodate future directions to improve the index as the global data landscape evolves